Deletion 9p and sex reversal. Issue 6 (June 1993) - Bennett, C P; Docherty, Z; Robb, S A; Ramani, P; Hawkins, J R; Grant, D
Abstract : We report a case of a female infant with a de novo deletion of the short arm of chromosome 9, sex reversal, and an apparently intact SRY gene. Sex reversal has been reported in a number of subjects with a normal Y chromosome and a deletion of the terminal segment of the short arm of chromosome 9. The factors controlling early development of the male testes are unknown. There are likely to be many genes involved and we present additional evidence that one of these is situated on the end of the short arm of chromosome 9.